The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1099/vir.0.008508-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of human rhinovirus field strains isolated during surveillance of enteroviruses

Abstract: Human rhinoviruses (HRVs), which are the most frequent causative agents of acute upper respiratory tract infections, are abundant worldwide. We have identified HRV strains in environmental specimens collected in Finland, Latvia and Slovakia during the surveillance of polioand other enteroviruses. These acid-sensitive HRV strains were isolated under conditions optimized for growth of most of the enteroviruses, i.e. in stationary human rhabdomyosarcoma cells incubated at 36 6C. Phylogenetic analysis of the seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 77 publications
2
20
0
Order By: Relevance
“…The frequent detection and high viral loads of HRV in fecal samples in the current study is consistent with the frequent detection of HRV by virus isolation during environmental screening of human sewage [Blomqvist et al, 2009]. It was speculated that the HRV variants derived from respiratory secretions carried into sewage by discarded used tissues or in wastewater.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The frequent detection and high viral loads of HRV in fecal samples in the current study is consistent with the frequent detection of HRV by virus isolation during environmental screening of human sewage [Blomqvist et al, 2009]. It was speculated that the HRV variants derived from respiratory secretions carried into sewage by discarded used tissues or in wastewater.…”
Section: Discussionsupporting
confidence: 89%
“…Experimentally, HRVs differ from enteroviruses in being inactivated at pH of <5 as well as pH values above 9–10. For this reason, HRV detection in fecal samples or sewage has generally been attributed in the past to swallowed respiratory secretions [Blomqvist et al, 2009]. In our opinion, this is unlikely for two reasons; firstly, the acid lability of HRVs that destroys their infectivity when passing through the stomach would lead to HRV RNA degradation if the virion capsid was breached.…”
Section: Discussionmentioning
confidence: 98%
“…One possible explanation could be that human rhinoviruses derived from respiratory secretions were carried into the canal by discarded used tissues or leaking sewage. More recently, the identification of HRV‐A in sewage specimens collected from Finland, Latvia and Slovakia has been reported for the first time (Blomqvist et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Predictions of infrequent recombination among the HRVs [ 83 ] have been made based on examination of the available set of HRV coding and noncoding regions [ 152 ]. Intensive analyses reported that recombination is not a driving force for the evolution of HRV types [ 144 , 153 , 154 ].…”
Section: And 3cmentioning
confidence: 99%